Інформаційні технології та когнітивна економіка: психологічний вимір управлінських рішень - Єременко, Денис Володимирович; Yeremenko, Denys; Єременко, Лариса В'ячеславівна; Yeremenko, Larysa (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті досліджено вплив когнітивних технологій на трансформацію бізнесу в умовах цифрової економіки. Розглянуто зміну ролі інтелектуальної праці, що стає центральним чинником розвитку сучасних підприємств. Акцент зроблено на використанні цифрової аналітики, штучного інтелекту, систем підтримки прийняття рішень та управління знаннями. Проаналізовано сучасні наукові підходи до впровадження технологій Індустрії 4.0 в управлінську практику. Особливу увагу приділено ролі людського капіталу та міждисциплінарної взаємодії як умов ефективної цифрової трансформації. Запропоновано концептуальні засади адаптації бізнес-моделей до нової економіки знань із врахуванням когнітивних чинників, а також підкреслено значення інноваційного потенціалу. /// EN: The article investigates the transformative impact of cognitive technologies on business processes within the framework of the digital economy, highlighting their capacity to redefine strategic decision-making. In response to the accelerating pace of change, modern enterprises face increasing levels of complexity, uncertainty, and the demand for innovation, prompting a shift away from rigid industrial models toward knowledge-driven paradigms. Cognitive technologies–such as artificial intelligence, machine learning, natural language processing, and big data analyticsenable organizations not only to automate repetitive tasks but also to support advanced decision-making by modeling complex scenarios, identifying hidden patterns, and predicting outcomes. The study emphasizes how these technologies are being integrated into financial operations, supply chain management, human capital development, and customer experience design. Furthermore, the article underscores the psychological dimension of digital transformation, focusing on how cognitive load, decision fatigue, and human trust in intelligent systems influence the adoption of AI-based tools. It highlights the growing importance of digital literacy, interdisciplinary collaboration, and leadership agility in creating organizational cultures capable of embracing rapid change. Based on a comprehensive review of contemporary research and applied business practices, the article develops a conceptual framework for embedding cognitive systems into corporate strategies. The framework supports sustainable innovation, resilience, and competitive advantage, while addressing key challenges such as ethical considerations, data governance, and employee readiness. Ultimately, the study advocates a human-centered approach where the synergy between cognitive technologies and human capabilities drives value creation, continuous learning, and strategic renewal in the digital era. The article concludes by stressing the need for ongoing psychological research to better align cognitive tools with user behavior and decision-making dynamics.
Information technologies and cognitive economy: the psychological dimension of managerial decision-making
Keywords: когнітивні технології; цифрова трансформація; управління знаннями; Індустрія 4.0; бізнес аналітика; людський капітал; інновації; стратегічне управління; цифровізація; штучний інтелект; cognitive technologies; digital transformation; knowledge management; Industry 4.0; business analytics; human capital; innovation; strategic management; digitalization; artificial intelligence